A COMPARATIVE STUDY OF LULA’S DIPLOMACY IN THE MIDDLE EAST AND AHMADINEJAD IN LATIN AMERICA - Souza, Bruno Mendelski de (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The article compares Lula’s foreign policy to the Middle East with Ahmadinejad’s to Latin America. Methodologically, the historical concepts of each diplomacy is combined with empirical data on trade flows and diplomatic actions. It is argued that the implementation of foreign policies involved similar (presidential diplomacy) and distinct means (universalism and multilateralism by Brazil, and personalism, bilateralism and low institutionalization by Iran). The results of diplomacies also resembled: although the economic implications were modest, Brasilia politically increased its global projection capacity, while Tehran relatively reduced its international isolation.